Coming soon to theaters Uncharted, Lost Planet, Mass Effect, Everquest. - Gaudiosi, John (Gamepro)
Hollywood has an abysmal track record with its video-game adaptations. Producer Ari Arad hopes to change that with his upcoming films that he hopes are just as spectacular to watch as the game are to play.